1998
DOI: 10.1177/107110079801900106
|View full text |Cite
|
Sign up to set email alerts
|

Rearfoot-Forefoot Orientation and Traumatic Risk for Runners

Abstract: Factors making runners more susceptible to injuries were identified with a comparative study between a healthy control group (216) and runners (66) suffering from overuse pathology. On static and dynamic footprint, the angles alpha0 (static) and alpha1 (dynamic) between heel and forefoot have been measured. Analysis showed that the injured subjects have a more pronated foot than control group subjects. These results suggest that the pronating foot configuration would be an injury risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 16 publications
0
31
1
Order By: Relevance
“…Of the nine studies, six involved sporting populations,3 25 26 2830 and three involved military recruits 15 19 27. The three military studies were limited to male participants, while the athlete studies had cohorts comprising both male and female participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the nine studies, six involved sporting populations,3 25 26 2830 and three involved military recruits 15 19 27. The three military studies were limited to male participants, while the athlete studies had cohorts comprising both male and female participants.…”
Section: Resultsmentioning
confidence: 99%
“…The three military investigations were all prospective studies, with follow-up periods ranging from 3.519 to 24 months 27. The six athlete studies were retrospective designs 3 25 26 2830. The number of TSIs reported ranged from 630 to 157 3.…”
Section: Resultsmentioning
confidence: 99%
“…Reinking 39 Numerous researchers have examined risk factors associated with "lower extremity overuse injuries," including ERLP 5,10,13,15,16,18,20,21,26,27,33,44,49,52 ; however, these results are not specific to ERLP and have focused primarily on adult recreational runners and military recruits. Limited research has examined risk factors associated with general lower extremity overuse conditions or ERLP specifically in collegiate athletes.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has reported that increasing age, female gender, previous injury, high BMI, low fitness level, foot posture, and excessive training distance are associated with injury [1][2][3]. Previous research has also suggested that pronation or pronation rate may be associated with injury [4,5], and this belief has led to the development of running shoes aimed at reducing pronation (e.g., motion control shoes). However, the effects of footwear on pronation are not fully understood.…”
Section: Introductionmentioning
confidence: 95%